5.
Let x be the age of the father and y be the age of the son. As of today, he's 3 times older, so we have
![x=3y](https://img.qammunity.org/2020/formulas/mathematics/high-school/sg07r1wzmjbqhd3ks1xnntg3chno5yqv33.png)
10 years ago their ages were, respectively, x-10 and y-10, and the father was 5 times older:
![x-10 = 5(y-10)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u69ogpn1lybvckfywyomady7nos3ep1mnv.png)
So, we have the system
![\begin{cases} x=3y\\x-10=5(y-10)\end{cases}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/93jp30cy3z9ghuunhj2psg3dxxcaj9g8hi.png)
Using the first equation, we can substitute every occurrence of "x" with "3y" in the second equation:
![3y-10=5(y-10) \iff 3y-10=5y-50 \iff 2y = 40 \iff y=20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9769tab8xsc7gy2b80ndtbkyhzjqad261s.png)
So, the son is 20 years old, which means that the father is 60 years old.
Indeed, 10 years ago they were 10 and 50 years old, so the father was 5 times older.
6.
Let x be the age of the grandfather and y the age of the granddaughter. We know that the grandfather is 10 times older:
![x=10y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fsati6gvjqsbfxougk1btgzumgojjcnznu.png)
He also is 54 years older:
![x=y+54](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6w29l69ve39nnv7qunvgu930rq3q0pnbw8.png)
Again, if we substitute x=10y in the second equation we have
![10y=y+54 \iff 9y=54 \iff y=6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/al1abgihhznh6jjzsoukui9w40bmk62tj6.png)